[P3Se4]+: A Binary Phosphorus–Selenium Cation. Issue 27 (8th May 2015) - Feldmann, Kai‐Oliver; Wiegand, Thomas; Ren, Jinjun; Eckert, Hellmut; Breternitz, Joachim; Groh, Matthias F.; Müller, Ulrike; Ruck, Michael; Maryasin, Boris; Ochsenfeld, Christian; Schön, Oliver; Karaghiosoff, Konstantin; et al.
Abstract Although a fairly large number of binary group 15/16 element cations have been reported, no example involving phosphorus in combination with a group 16 element has been synthesized and characterized to date. In this contribution is reported the synthesis and structural characterization of the first example of such a cation, namely a nortricyclane‐type [P3Se4]+. This cation has been independently discovered by three groups through three different synthetic routes, as described herein. The molecular and electronic structure of the [P3Se4]+ cage and its crystal properties in the solid state have been characterized comprehensively by using X‐ray diffraction, Raman, and nuclear magnetic resonance spectroscopies, as well as quantum chemical calculations.